Fireproof temperature-resistant special tempered glass and preparation method thereof

By using cesium hydroxide, potassium hydroxide pretreatment and zinc sulfate spraying in borosilicate glass, the problem of insufficient ion exchange during chemical tempering is solved, significantly improving its fire resistance and temperature resistance and reducing self-destruction rate.

CN119612981AInactive Publication Date: 2025-03-14CHANGZHOU GOLDEN CENTURY GLASS TECH CO LTD

Patent Information

Application Number
CN202411820063.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the chemical tempering process, the existing high borosilicate glass has a low alkali metal ion content and a small thermal expansion coefficient, resulting in low ion exchange amount and shallow exchange depth, which has a safety hazard of high self-destruction rate and poor fire and temperature resistance.

Method used

By pretreating the substrate glass in a mixed solution of cesium hydroxide and potassium hydroxide, more new diffusion ion channels are formed to speed up the ion exchange rate, and spray zinc sulfate before physical tempering to reduce nickel sulfide, thereby improving the strength and fire resistance of the glass.

Benefits of technology

It significantly improves fire resistance and high temperature resistance, reduces the self-destruction rate of tempered glass, and maintains the light transmittance and surface flatness of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182887360000081
    Figure BDA0005182887360000081
  • Figure BDA0005182887360000091
    Figure BDA0005182887360000091
  • Figure BDA0005182887360000092
    Figure BDA0005182887360000092
Patent Text Reader

Abstract

The invention discloses a preparation method of fireproof temperature-resistant special tempered glass, which comprises the following steps: pretreating substrate glass by using a mixed solution of cesium hydroxide and potassium hydroxide, with the cesium hydroxide content of 0.2-15 wt% and the potassium hydroxide content of 0.5-10 wt%; substrate glass is placed in the mixed solution of cesium hydroxide and potassium hydroxide, the mixed solution is placed in a micro-high-pressure environment for 0.5-1 hour, and the micro-high pressure is 10-15 MPa; basic glass is pretreated through a cesium hydroxide and potassium hydroxide mixed solution, under the synergistic effect of cesium hydroxide and potassium hydroxide, a hydroxyl layer on the surface of the glass is more easily removed, a silicon-oxygen network structure is damaged, a silicon-oxygen network is broken, more new diffusion ion channels are formed, and the ion exchange speed is increased; pretreatment is carried out in a micro-high-pressure environment, so that the substrate glass pretreatment speed can be increased, and the pretreatment time is remarkably shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass production, and in particular to fire-proof and heat-resistant special tempered glass and a preparation method thereof. Background Art

[0002] Glass is a common type of inorganic non-metallic material. Compared with ceramic materials, glass materials are generally weaker in strength. Glass-ceramics is a relatively unique type of glass. By adding a nucleating agent to induce nucleation, a large number of micro-nano crystals are formed inside the glass, thereby achieving reinforcement and toughening.

[0003] Tempered glass is a glass with compressive stress on the surface, also known as strengthened glass. The tempering method for strengthening glass began in France in 1874. Tempered glass is actually a prestressed glass. In order to improve the strength of the glass, chemical or physical methods are usually used to form compressive stress on the glass surface. When the glass is subjected to external force, the surface stress is first offset, thereby improving the bearing capacity and enhancing the glass's own resistance to wind pressure, cold and heat, impact, etc. The process of tempered glass is usually divided into physical tempering and chemical tempering. Physical tempering is to heat high-quality float glass to a softening point and then rapidly cool the glass surface so that the compressive stress is distributed on the glass surface, while the tensile stress is in the center layer. Because there is a strong and equal compressive stress, the tensile stress generated by the external pressure is offset by the strong compressive stress of the glass, thereby increasing the safety of the glass. However, physical tempering has strict requirements on the thickness and shape of the glass (the thickness is usually above 3mm), and the cooling speed is slow and the energy consumption is high. Chemical tempering is an ion exchange process that uses an ion exchange process to exchange alkali metal ions with smaller radius in the glass surface layer with ions with larger radius in the solution in an alkali salt in a range not higher than the glass transition temperature, thereby forming compressive stress on the glass surface layer. Physical tempering is usually used for high borosilicate glass, but at present, when chemical tempering is used for high borosilicate glass, due to its low alkali metal ion content and small thermal expansion coefficient, the ion exchange amount is low and the exchange depth is shallow during the ion exchange process, resulting in a high self-explosion rate and a safety hazard.

[0004] Ordinary tempered glass can withstand the thermal stress generated by rapid cooling and heating, and thus has a certain fireproof function. Although ordinary tempered glass has a certain fireproof function, its fireproof performance is not high and it cannot be used as fireproof glass because its surface compressive stress is not high enough, its strength is not high enough, and its temperature resistance is not good enough. Summary of the invention

[0005] An object of the present invention is to solve the above-mentioned problems and provide a fire-resistant and heat-resistant special tempered glass and a preparation method thereof, so as to increase the ion exchange capacity and exchange depth, significantly improve the fire-resistant and high-temperature and low-temperature performance, significantly reduce nickel sulfide, and thus greatly reduce the self-explosion rate of tempered glass.

[0006] To achieve the above purpose, the technical solution provided by the present invention is:

[0007] In a first aspect of the present invention, a method for preparing fireproof and heat-resistant special tempered glass is provided, comprising pretreating a base glass using a mixed solution of cesium hydroxide and potassium hydroxide, wherein the cesium hydroxide is 0.2-15wt% and the potassium hydroxide is 0.5-10wt%. The base glass is generally borosilicate glass.

[0008] Preferably, the pretreatment further comprises placing the substrate glass in the mixed solution of cesium hydroxide and potassium hydroxide for 0.5-1 hour under a slightly high pressure environment, wherein the slightly high pressure is 10-15 MPa.

[0009] Preferably, the substrate glass pretreatment temperature does not exceed 100°C.

[0010] Preferably, the preparation method further comprises first chemically tempering the steel sheet by rapidly heating the steel sheet to 450-550° C., and then, after the chemical tempering is completed, heating the steel sheet to 700-780° C. for physical tempering.

[0011] Preferably, the process before physical tempering also includes uniformly spraying a layer of zinc salt on the surface of the glass layer.

[0012] Preferably, the tempered molten salt includes potassium salt, lithium salt and cesium salt, and the weight ratio of potassium salt, lithium salt and cesium salt is 0.5-1:1-2:0.1-0.5.

[0013] Preferably, the potassium salt is one or more of potassium nitrate, potassium carbonate, potassium sulfate, and potassium chloride; the lithium salt is one or more of lithium nitrate, lithium carbonate, lithium sulfate, and lithium chloride; and the cesium salt is one or more of cesium nitrate, cesium carbonate, cesium sulfate, and cesium chloride.

[0014] Preferably, the preparation method comprises the following steps:

[0015] Step 1: pre-treating the substrate glass with a mixed solution of cesium hydroxide and potassium hydroxide, placing it at a slightly high pressure of 10-15 MPa and a temperature of 75-95° C. for 0.5-1 hour, and then drying the glass to obtain pre-treated glass;

[0016] Step 2: Apply a layer of tempered molten salt to the pre-treated glass, and raise the temperature to 500-530°C for chemical tempering for 1-2 hours;

[0017] Step 3: Spray a layer of zinc sulfate on the chemically tempered glass, and heat the glass to 760-770°C for physical tempering for 1-2 hours;

[0018] Step 4: Rapidly cool the physically tempered glass to obtain the tempered glass.

[0019] Preferably, the zinc sulfate coating thickness is 0.1-0.5 mm.

[0020] Another aspect of the present invention provides a tempered glass obtained by the method for preparing the fire-resistant and heat-resistant special tempered glass.

[0021] The beneficial effects of the present invention are as follows:

[0022] (1) The present invention pre-treats the base glass with a mixed solution of cesium hydroxide and potassium hydroxide. Under the synergistic effect of cesium hydroxide and potassium hydroxide, it is easier to remove the hydroxyl layer on the surface of the glass, destroy the silicon-oxygen network structure to break the silicon-oxygen network, form more new diffusion ion channels to accelerate the ion exchange rate, and at the same time, the pre-treatment is carried out in a slightly high-pressure environment to accelerate the pre-treatment rate of the base glass and significantly shorten the pre-treatment time. Compared with acid treatment, the base glass pre-treated with the mixed solution of cesium hydroxide and potassium hydroxide can be tempered without cleaning and drying, thereby reducing the cleaning steps and improving production efficiency. At the same time, the glass breakage caused by the rapid heating of the base glass during the tempering process due to insufficient drying is reduced. Secondly, the cesium hydroxide and potassium hydroxide remaining on the surface of the glass after the pre-treatment with the mixed solution of cesium hydroxide and potassium hydroxide are used for ion exchange during the chemical tempering process, which can increase the ion exchange depth and form a huge compressive stress on the glass surface, significantly improve the strength of the tempered glass, and enhance the fire resistance and temperature resistance of the tempered glass.

[0023] (2) In the present invention, the specific surface area of ​​the base glass is increased after pretreatment, and the compressive stress is dispersed, which significantly improves the strength of the tempered glass. However, the surface of the tempered glass obtained after pretreatment is rough and easily corroded by acids and alkalis, which affects the light transmittance of the tempered glass. The present invention adopts physical tempering at a temperature of 760-770°C, which can significantly reduce the influence of the pretreated base glass on the light transmittance of the tempered glass and maintain the surface flatness of the glass.

[0024] (3) The present invention sprays zinc sulfate before physical tempering, wherein zinc ions are exchanged with nickel ions of nickel sulfide in the glass, thereby reducing nickel sulfide, thereby reducing the self-explosion of the tempered glass caused by the phase change of nickel sulfide, significantly improving the strength of the glass, achieving better fire resistance and temperature resistance, and reducing the self-explosion rate. DETAILED DESCRIPTION

[0025] The substrate glass, cesium hydroxide, potassium hydroxide and other materials used in the present invention are all purchased from the market.

[0026] In one embodiment of the present invention, borosilicate glass is selected as the base glass, and the base glass is pretreated by immersing it in a mixed solution containing 0.2-15 wt % cesium hydroxide and 0.5-10 wt % potassium hydroxide.

[0027] In another embodiment, the substrate glass is pretreated by placing it in a sealable space to the mixed solution of cesium hydroxide and potassium hydroxide, and then pressurizing the sealed space to a slightly high pressure of 10-15 MPa, and placing it for 0.5-1 hour to obtain the pretreated glass. The pressurization can be performed by a common pressurizer, and more preferably, it is performed under nitrogen protection.

[0028] In another embodiment, the temperature of the base glass during the pretreatment process does not exceed 100°C, and a more preferred temperature is 75-95°C. Using a mixed solution of cesium hydroxide and potassium hydroxide to treat the base glass at too high a temperature will result in over-treatment and thus reduce the strength of the base glass, but too low a temperature will slow down the pretreatment speed. The pretreatment is suitable at a temperature of 75-95°C, which was accidentally discovered by the inventor during the experiment.

[0029] In another embodiment, the temperature is rapidly raised to 450-550°C for chemical tempering, and then the temperature is raised to 700-780°C for physical tempering after the chemical tempering is completed. The present invention first uses chemical tempering for ion exchange, and after the ion exchange, a more stable network structure is formed on the surface and deeper layers of the glass, and then physical tempering is performed at a higher temperature, which can increase the surface prestress while increasing the light transmittance of the glass.

[0030] In another embodiment, a certain amount of zinc salt is sprayed on the glass surface by a nozzle before physical tempering to form a uniform film, wherein the zinc salt may include but is not limited to one or more of zinc sulfate, zinc chloride, zinc carbonate, and zinc nitrate.

[0031] In another embodiment, a tempering agent, i.e., tempering molten salt, is used in the process of chemical tempering. Generally, a mixture of potassium salt and lithium salt is used. In the present invention, a cesium salt is added. Since the radius of cesium ions is large, they are easier to exchange and can also deepen the depth of ion exchange. The weight ratio of the potassium salt, lithium salt, and cesium salt is 0.5-1:1-2:0.1-0.5. Preferably, the weight ratio of the potassium salt, lithium salt, and cesium salt is 0.5:1.2:0.3.

[0032] In another embodiment, the potassium salt may include but is not limited to one or more of potassium nitrate, potassium carbonate, potassium sulfate, and potassium chloride; the lithium salt may include but is not limited to one or more of lithium nitrate, lithium carbonate, lithium sulfate, and lithium chloride; the cesium salt may include but is not limited to one or more of cesium nitrate, cesium carbonate, cesium sulfate, and cesium chloride, preferably a combination of potassium nitrate, lithium carbonate, and cesium sulfate.

[0033] In another embodiment, the method for preparing the fire-resistant and heat-resistant tempered glass of the present invention specifically comprises the following steps:

[0034] Step 1: pre-treating the substrate glass with a mixed solution of cesium hydroxide and potassium hydroxide, placing it at a slightly high pressure of 10-15 MPa and a temperature of 75-95° C. for 0.5-1 hour, and then drying the glass to obtain pre-treated glass;

[0035] Step 2: Apply a layer of tempered molten salt to the pre-treated glass, raise the temperature to 500-530°C for chemical tempering for 1-2 hours; the thickness of the tempered molten salt is determined according to the thickness of the glass, generally 5%-10% of the thickness of the glass.

[0036] Step 3: Spray a layer of zinc sulfate on the chemically tempered glass, and heat the glass to 760-770°C for physical tempering for 1-2 hours;

[0037] Step 4: Rapidly cool the physically tempered glass to obtain the tempered glass.

[0038] In another embodiment, the zinc sulfate sprayed before physical tempering has a thickness of 0.1-0.5 mm, preferably 0.2 mm. The exchange effect of zinc ions and nickel ions is best at this thickness. After the zinc ions and nickel ions are exchanged, zinc sulfide with stable crystal phase is formed, which reduces the presence of nickel sulfide in the glass, thereby reducing the self-explosion rate of the tempered glass.

[0039] Unless otherwise defined herein, the scientific and technical terms used herein have the same meanings as those understood and commonly used by those skilled in the art.

[0040] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any particular theory or mechanism. In this article, all features defined in the form of numerical ranges or percentage ranges, such as quantity, value, concentration and content, are only for the sake of brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have covered and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0041] The above features mentioned in the present invention or the features mentioned in the embodiments can be combined in any way. All features disclosed in this specification can be used in combination with any combination form, and as long as there is no contradiction in the combination of these features, all possible combinations should be considered to be within the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.

[0042] The present invention is further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually performed under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise specified, all percentages, ratios, proportions, or parts are by weight. The units mentioned in the weight percentages in the present invention are well known to those skilled in the art. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the recorded content can be applied to the method of the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.

[0043] Example 1

[0044] Borosilicate glass is selected as the base glass, and the base glass is immersed in a mixed solution containing 0.2wt% cesium hydroxide and 0.5wt% potassium hydroxide, and pretreated at room temperature and pressure for 0.5 hour; a layer of tempering agent is applied to the pretreated glass, the tempering agent is a tempering molten salt mixed with potassium nitrate, lithium carbonate, and cesium sulfate, the coating thickness of the tempering molten salt is 5% of the glass thickness, and the weight ratio of potassium nitrate, lithium carbonate, and cesium sulfate is 0.5:1:0.1, and the temperature is raised to 500°C in a furnace for chemical tempering for 1 hour; a layer of zinc sulfate is sprayed on the chemically tempered glass, the thickness of the zinc sulfate is 0.1mm, and the temperature is raised to 760°C for physical tempering for 1 hour; the physically tempered glass is rapidly cooled to obtain the tempered glass.

[0045] Example 2

[0046] Borosilicate glass is selected as the base glass, and the base glass is pretreated by immersing it in a mixed solution containing 15wt% cesium hydroxide and 10wt% potassium hydroxide. The base glass pretreatment is placed in a sealable space at a micro-high pressure of 10MPa and a temperature of 75°C for 0.5 hours, and then the glass is dried to obtain the pretreated glass; a layer of tempered molten salt potassium nitrate, lithium carbonate, and cesium sulfate is applied to the pretreated glass, the weight ratio of potassium nitrate, lithium carbonate, and cesium sulfate is 1:2:0.5, and the coating thickness of the tempered molten salt is 10% of the glass thickness, the temperature is increased to 530°C for chemical tempering for 2 hours; a layer of zinc sulfate is sprayed on the chemically tempered glass, the thickness of the zinc sulfate is 0.1mm, and the temperature is increased to 780°C for physical tempering for 2 hours; the physically tempered glass is rapidly cooled to obtain the tempered glass.

[0047] Example 3

[0048] Borosilicate glass is selected as the base glass, and the base glass is immersed in a mixed solution containing 5wt% cesium hydroxide and 2wt% potassium hydroxide for pretreatment. The base glass pretreatment is placed in a sealable space at a micro-high pressure of 15MPa and a temperature of 95°C for 0.8 hours, and then the glass is dried to obtain the pretreated glass; a layer of tempered molten salt potassium nitrate, lithium carbonate, and cesium sulfate is applied to the pretreated glass, the weight ratio of potassium nitrate, lithium carbonate, and cesium sulfate is 0.7:1.5:0.3, the coating thickness of the tempered molten salt is 10% of the glass thickness, the temperature is increased to 520°C for chemical tempering, and the time is 1.5 hours; a layer of zinc sulfate is sprayed on the chemically tempered glass, the thickness of the zinc sulfate is 0.5mm, the temperature is increased to 700°C for physical tempering, and the time is 1.5 hours; the physically tempered glass is rapidly cooled to obtain the tempered glass.

[0049] Example 4

[0050] Borosilicate glass is selected as the base glass, and the base glass is pretreated by immersing it in a mixed solution containing 10wt% cesium hydroxide and 3wt% potassium hydroxide. The base glass pretreatment is placed in a sealable space at a micro-high pressure of 11MPa and a temperature of 85°C for 0.5 hours, and then the glass is dried to obtain the pretreated glass; a layer of tempered molten salt potassium nitrate, lithium carbonate and cesium sulfate is applied to the pretreated glass, the weight ratio of potassium nitrate, lithium carbonate and cesium sulfate is 0.5:1.2:0.3, the coating thickness of the tempered molten salt is 8% of the glass thickness, the temperature is increased to 500°C for chemical tempering, and the time is 1 hour; a layer of zinc sulfate with a thickness of 0.2mm is sprayed on the chemically tempered glass, and the temperature is increased to 770°C for physical tempering, and the time is 2 hours; the physically tempered glass is rapidly cooled to obtain the tempered glass.

[0051] Example 5

[0052] Borosilicate glass is selected as the base glass, and the base glass is pretreated by immersing it in a mixed solution containing 10wt% cesium hydroxide and 3wt% potassium hydroxide. The base glass pretreatment is placed in a sealable space at a micro-high pressure of 11MPa and a temperature of 85°C for 0.5 hours, and then the glass is dried to obtain the pretreated glass; a layer of tempered molten salt potassium carbonate, lithium carbonate and cesium carbonate is applied to the pretreated glass, and the weight ratio of potassium carbonate, lithium carbonate and cesium carbonate is 0.5:1.2:0.3, and the coating thickness of the tempered molten salt is 8% of the glass thickness; the temperature is increased to 500°C for chemical tempering for 1 hour; a layer of zinc sulfate with a thickness of 0.2mm is sprayed on the chemically tempered glass, and the temperature is increased to 770°C for physical tempering for 2 hours; the physically tempered glass is rapidly cooled to obtain the tempered glass.

[0053] Example 6

[0054] Borosilicate glass is selected as the base glass, and the base glass is pretreated by immersing it in a mixed solution containing 10wt% cesium hydroxide and 3wt% potassium hydroxide. The base glass pretreatment is placed in a sealable space at a micro-high pressure of 11MPa and a temperature of 85°C for 0.5 hours, and then the glass is dried to obtain the pretreated glass; a layer of tempered molten salt lithium sulfate, potassium sulfate and cesium sulfate is applied to the pretreated glass, and the weight ratio of lithium sulfate, potassium sulfate and cesium sulfate is 0.5:1.2:0.3, and the coating thickness of the tempered molten salt is 8% of the glass thickness, and the temperature is increased to 500°C for chemical tempering for 1 hour; a layer of zinc sulfate with a thickness of 0.2mm is sprayed on the chemically tempered glass, and the temperature is increased to 770°C for physical tempering for 2 hours; the physically tempered glass is rapidly cooled to obtain the tempered glass.

[0055] Example 7

[0056] Borosilicate glass is selected as the base glass, and the base glass is immersed in a mixed solution containing 10wt% cesium hydroxide and 3wt% potassium hydroxide for pretreatment. The base glass pretreatment is placed in a sealable space at a micro-high pressure of 11MPa and a temperature of 85°C for 0.5 hours, and then the glass is dried to obtain the pretreated glass; a layer of tempered molten salt potassium nitrate, lithium carbonate, and cesium sulfate is applied to the pretreated glass, the weight ratio of potassium nitrate, lithium carbonate, and cesium sulfate is 0.5:1.2:0.3, and the coating thickness of the tempered molten salt is 8% of the glass thickness; the temperature is increased to 500°C for chemical tempering for 1 hour; after chemical tempering, the temperature is increased to 770°C for physical tempering for 2 hours; the physically tempered glass is rapidly cooled to obtain the tempered glass.

[0057] Comparative Example 1

[0058] In Example 4, the following steps are omitted: "immersing the base glass in a mixed solution containing 10wt% cesium hydroxide and 3wt% potassium hydroxide for pretreatment, the base glass pretreatment is to place the glass in a sealable space at a slightly high pressure of 11MPa and a temperature of 85°C for 0.5 hours, and then drying the glass to obtain pretreated glass." The remaining steps are the same as in Example 4.

[0059] Comparative Example 2

[0060] In Example 4, the "mixed solution of 10 wt % cesium hydroxide and 3 wt % potassium hydroxide" is changed to "mixed solution of 5 wt % hydrofluoric acid", and the remaining steps are the same as those in Example 4.

[0061] The tempered glass obtained in the above embodiment and the comparative example was subjected to 1. bending strength test, the test standard is GB / T37781-2019 (glass material bending strength test method), the test method is three-point bending method; 2. surface stress test, the test standard is GB / T18144 (glass surface stress test method), the test method uses a surface tester, and the test results are as follows:

[0062]

[0063]

[0064] It can be seen from the above table that the bending strength and surface stress performance of the tempered glass of Examples 1-7 are significantly better than those of Comparative Examples 1 and 2, especially the bending strength and surface stress performance of the tempered glass of Example 4 are the best. It can be seen that the present invention can form a huge compressive stress on the glass surface, significantly improve the strength of the tempered glass, and enhance the fire resistance and temperature resistance of the tempered glass.

[0065] 3. Thermal shock resistance test: Test method: Place a 300×300mm glass test piece in an oven set at a certain temperature (200℃, 250℃, 300℃, 350℃, 400℃, 450℃, 500℃) and keep it warm for more than 4 hours. After taking out the test piece, immerse it vertically in 0℃ ice water. After 5 minutes, observe whether the glass surface is damaged (fish-scale peeling on the glass surface and edge is not considered damage).

[0066]

[0067]

[0068] It can be seen from the above test results that the test temperature of the thermal shock resistance performance of the embodiment of the present invention is at least 400°C, and the test temperature of the thermal shock resistance performance of comparative examples 1 and 2 is both 250°C. This shows that the temperature resistance performance of the tempered glass of the present invention is significantly improved.

[0069] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A method for preparing fireproof and heat-resistant special tempered glass, characterized in that: The method comprises pre-treating the substrate glass by using a mixed solution of cesium hydroxide and potassium hydroxide, wherein the cesium hydroxide is 0.2-15wt% and the potassium hydroxide is 0.5-10wt%.

2. The method for preparing fireproof and heat-resistant special tempered glass according to claim 1, characterized in that: The pretreatment specifically includes: placing the substrate glass in the mixed solution of cesium hydroxide and potassium hydroxide for 0.5-1 hour under a slightly high pressure environment, wherein the slightly high pressure is 10-15 MPa.

3. The method for preparing fireproof and heat-resistant special tempered glass according to claim 1 or 2, characterized in that: The substrate glass pretreatment temperature does not exceed 100°C.

4. The method for preparing fireproof and heat-resistant special tempered glass according to any one of claims 1 to 3, characterized in that: The method for preparing the tempered glass also includes: firstly chemically tempering the glass by rapidly heating it to 450-550° C., and then raising the temperature to 700-780° C. for physical tempering after the chemical tempering is completed.

5. The method for preparing fireproof and heat-resistant special tempered glass according to claim 4, characterized in that: The process before physical tempering also includes uniformly spraying a layer of zinc salt on the surface of the glass layer.

6. The method for preparing fireproof and heat-resistant special tempered glass according to claim 4, characterized in that: The tempering molten salt used in the chemical tempering includes potassium salt, lithium salt and cesium salt, and the weight ratio of the potassium salt, lithium salt and cesium salt is 0.5-1:1-2:0.1-0.

5.

7. The method for preparing fireproof and heat-resistant special tempered glass according to claim 6, characterized in that: The potassium salt is one or more of potassium nitrate, potassium carbonate, potassium sulfate, and potassium chloride; the lithium salt is one or more of lithium nitrate, lithium carbonate, lithium sulfate, and lithium chloride; and the cesium salt is one or more of cesium nitrate, cesium carbonate, cesium sulfate, and cesium chloride.

8. The method for preparing fireproof and heat-resistant special tempered glass according to claim 7, characterized in that: The preparation method comprises the following steps: Step 1: pre-treating the substrate glass with a mixed solution of cesium hydroxide and potassium hydroxide, placing it at a slightly high pressure of 10-15 MPa and a temperature of 75-95° C. for 0.5-1 hour, and then drying the glass to obtain pre-treated glass; Step 2: Apply a layer of tempered molten salt to the pre-treated glass, and raise the temperature to 500-530°C for chemical tempering for 1-2 hours; Step 3: Spray a layer of zinc sulfate on the chemically tempered glass, and heat the glass to 760-770°C for physical tempering for 1-2 hours; Step 4: Rapidly cool the physically tempered glass to obtain the tempered glass.

9. The method for preparing fireproof and heat-resistant special tempered glass according to claim 8, characterized in that: The zinc sulfate coating thickness is 0.1-0.5 mm.

10. Tempered glass obtained by the method for preparing fireproof and heat-resistant special tempered glass according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation process of high-strength single-sheet cesium potassium fireproof glass

    CN107311438A

  • Soda-lime-silica glass spray coating tempering treatment method

    CN108751745A

  • Toughened glass product and preparation method thereof, and electronic equipment

    CN111732343A

  • High transparent glass plate and method for producing high transparent glass plate

    CN1408663A

  • Tempered glass tube for discharge tube and discharge tube using the same glass tube

    JP2000072490A

Cited By

  • High-strength high-temperature-resistant fireproof industrial glass and preparation method thereof

    CN121342339A

  • Special tempered glass and preparation method thereof

    CN121698582A